The efficacy and safety of transcutaneous auricular vagus nerve stimulation for patients with minimally conscious state: a sham-controlled randomized double-blind clinical trial - Yifan Zhou; Yifan Zhou; Yejing Sun; Yejing Sun; Pei He; Pei He; Qi Xiong; Qi Xiong; Junwei Kang; Junwei Kang; Yunliang Tang; Yunliang Tang; et al. (Frontiers in Neuroscience, 2023)
BackgroundTranscutaneous auricular vagus nerve stimulation (taVNS) has emerged as a potentially effective neuromodulation technique for addressing neurological disorders, including disorders of consciousness. Expanding upon our prior clinical study, which demonstrated the superior effectiveness of a 4-week taVNS treatment in patients with minimally conscious state (MCS) compared to those in a vegetative state/unresponsive wakefulness state, the aim of this investigation was to evaluate the safety and therapeutic efficacy of taVNS in individuals with MCS through a sham-controlled randomized double-blind clinical trial.MethodsA cohort of 50 adult patients (male = 33, female = 17) diagnosed with a MCS were randomly assigned to either the active taVNS (N = 25) or sham taVNS (N = 25) groups. The treatment period lasted for 4 weeks, followed by an 8-week follow-up period. The Coma Recovery Scale-Revised (CRS-R) and Glasgow Coma Scale (GCS) were administered at baseline and weekly during the initial 4 weeks. Additionally, the Disability Rating Scale (DRS) was used to assess the patients’ functional abilities via telephone at week 12. Furthermore, various neurophysiological measures, including electroencephalogram (EEG), upper-limb somatosensory evoked potentials (USEP), brainstem auditory evoked potentials (BAEP), and P300 event-related potentials (P300), were employed to monitor changes in brain activity and neural conduction pathways.ResultsThe scores for the active taVNS group in the CRS-R and GCS showed greater improvement over time compared to the sham taVNS group (CRS-R: 1-week, Z = −1.248, p = 0.212; 2-week, Z = −1.090, p = 0.276; 3-week, Z = −2.017, p = 0.044; 4-week, Z = −2.267, p = 0.023. GCS: 1-week, Z = −1.325, p = 0.185; 2-week, Z = −1.245, p = 0.213; 3-week, Z = −1.848, p = 0.065; 4-week, Z = −1.990, p = 0.047). Additionally, the EEG, USEP, BAEP, and P300 also demonstrated significant improvement in the active taVNS group compared to the sham taVNS group at week 4 (EEG, Z = −2.086, p = 0.037; USEP, Z = −2.014, p = 0.044; BAEP, Z = −2.298, p = 0.022; P300 amplitude, Z = −1.974, p = 0.049; P300 latency, t = 2.275, p = 0.027). Subgroup analysis revealed that patients with MCS derived greater benefits from receiving taVNS treatment earlier (CRS-R, Disease duration ≤ 1-month, mean difference = 8.50, 95% CI = [2.22, 14.78], p = 0.027; GCS, Disease duration ≤ 1-month, mean difference = 3.58, 95% CI = [0.14, 7.03], p = 0.044). By week 12, the active taVNS group exhibited lower Disability Rating Scale (DRS) scores compared to the sham taVNS group (Z = −2.105, p = 0.035), indicating a more favorable prognosis for MCS patients who underwent taVNS. Furthermore, no significant adverse events related to taVNS were observed during treatment.ConclusionThe findings of this study suggest that taVNS may serve as a potentially effective and safe intervention for facilitating the restoration of consciousness in individuals diagnosed with MCS. This therapeutic approach appears to enhance cerebral functioning and optimize neural conduction pathways.Clinical trial registrationhttp://www.chictr.org.cn, Identifier ChiCTR2200066629.